Circulating tumor cell markers for early detection and drug resistance assessment through liquid biopsy - Yadav, Priya; Rajendrasozhan, Saravanan; Lajimi, Ramzi Hadj; Patel, Raja Ramadevi; Heymann, Dominique; Prasad, N. Rajendra (Frontiers in Oncology, 2025)
Circulating tumor cells (CTCs) are cancerous cells that extravasate from the primary tumor or metastatic foci and travel through the bloodstream to distant organs. CTCs provide crucial insights into cancer metastasis, the evolution of tumor genotypes during treatment, and the development of chemo- and/or radio-resistance during disease progression. The process of Epithelial-to-mesenchymal transition (EMT) plays a key role in CTCs formation, as this process enhances cell’s migration properties and is often associated with increased invasiveness thereby leading to chemotherapy resistance. During the EMT process, tumor cells lose epithelial markers like EpCAM and acquire mesenchymal markers such as vimentin driven by transcription factors like Snail and Twist. CTCs are typically identified using specific cell surface markers, which vary depending on the cancer type. Common markers include EpCAM, used for epithelial cancers; CD44 and CD24, which are associated with cancer stem cells; and cytokeratins, such as CK8 and CK18. Other markers like HER2/neu and vimentin can also be used to target CTCs in specific cancer types and stages. Commonly, immune-based isolation techniques are being implemented for the isolation and enrichment of CTCs. This review emphasizes the clinical relevance of CTCs, particularly in understanding drug resistance mechanisms, and underscores the importance of EMT-derived CTCs in multidrug resistance (MDR). Moreover, the review also discusses CTCs-specific surface markers that are crucial for their isolation and enrichment. Ultimately, the EMT-specific markers found in CTCs could provide significant information to halt the disease progression and enable personalized therapies.